2019
DOI: 10.1111/jon.12620
|View full text |Cite
|
Sign up to set email alerts
|

The Role of FDG‐PET in Patients with Epilepsy Related to Periventricular Nodular Heterotopias: Diagnostic Features and Long‐Term Outcome

Abstract: BACKGROUND AND PURPOSE: Periventricular nodular heterotopias (PNHs) are frequently associated with drug-resistant epilepsy (DRE). Although magnetic resonance imaging (MRI) can define the morphological features of PNHs, still there is a need to assess their metabolic activity in order to provide useful information on epileptogenicity and long-term outcome. To that end, we investigated the ability of 18 F-FDG PET to identify seizure onset zone in order to assess the metabolic activity of the ectopic neurons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…12,23,25,26 However, there is scarce and, to some extent, conflicting evidence regarding the utility of 18 F-FDG PET/CT in GMH patients. 24,27 For instance, Mirandola et al 27 observed no correlation between PET/CT and SEEG, while Popescu et al 24 documented that PET/CT had high sensitivity in detecting seizure onset zone and had a high correlation with SEEG. Popescu et al 24 concluded that MRI and 18 F-FDG PET/ CT contributed to detecting EZ, determining the place of invasive electrodes, and increasing the chance of seizure freedom after epilepsy surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,23,25,26 However, there is scarce and, to some extent, conflicting evidence regarding the utility of 18 F-FDG PET/CT in GMH patients. 24,27 For instance, Mirandola et al 27 observed no correlation between PET/CT and SEEG, while Popescu et al 24 documented that PET/CT had high sensitivity in detecting seizure onset zone and had a high correlation with SEEG. Popescu et al 24 concluded that MRI and 18 F-FDG PET/ CT contributed to detecting EZ, determining the place of invasive electrodes, and increasing the chance of seizure freedom after epilepsy surgery.…”
Section: Discussionmentioning
confidence: 99%
“…24,27 For instance, Mirandola et al 27 observed no correlation between PET/CT and SEEG, while Popescu et al 24 documented that PET/CT had high sensitivity in detecting seizure onset zone and had a high correlation with SEEG. Popescu et al 24 concluded that MRI and 18 F-FDG PET/ CT contributed to detecting EZ, determining the place of invasive electrodes, and increasing the chance of seizure freedom after epilepsy surgery. The present work furthered the latter study by using a hybrid PET/MRI scan and mirroring their findings by showing the yields of 18 F-FDG PET/MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the incidence of cerebrovascular disease, dementia, and neurodegenerative diseases has increased with the aging of the Chinese population. Moreover, the incidence of epilepsy in the elderly shows an upward trend [2]. According to the location of abnormal discharge of neurons and the range of discharge, the main clinical manifestations are the different dysfunctions, including different motor, sensory, cognitive, and autonomic nerve [3].…”
Section: Introductionmentioning
confidence: 99%